2014
DOI: 10.1037/a0034213
|View full text |Cite
|
Sign up to set email alerts
|

Prompting healthier eating: Testing the use of health and social norm based messages.

Abstract: For the promotion of healthy eating, social norm messages may be more effective than health messages for consumers failing to adhere to dietary guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 36 publications
10
144
2
1
Order By: Relevance
“…Descriptive norms seem to be a strong and stable predictor of healthy and sustainable consumption, while the impact of injunctive norms seems to be weaker and less consistent [33][34][35]. A positive interaction between descriptive and injunctive norms for sustainable consumption has also been reported [16].…”
Section: Social Norm Approaches To Promote Pro-environmental Decisionmentioning
confidence: 92%
See 1 more Smart Citation
“…Descriptive norms seem to be a strong and stable predictor of healthy and sustainable consumption, while the impact of injunctive norms seems to be weaker and less consistent [33][34][35]. A positive interaction between descriptive and injunctive norms for sustainable consumption has also been reported [16].…”
Section: Social Norm Approaches To Promote Pro-environmental Decisionmentioning
confidence: 92%
“…Social norm interventions are typically implemented using signs displaying a normative message [14,34,35]. For example, hotel guests have been asked to reuse their towels by a message written on door hangers [36], park visitors have been invited not to steal petrified wood by signs installed in the park [15], public toilet users have been asked to switch off the light by means of colorful prompts [37], and consumers have been informed about the health food choices of other consumers via signs installed on the shopping basket [35,38].…”
Section: Social Norm Approaches To Promote Pro-environmental Decisionmentioning
confidence: 99%
“…Lally et al (55) found that perceptions of peers' attitudes towards consuming different food types did not predict intake, whereas perceptions of what peers were eating were predictive. Mollen et al (62) too found no evidence that an injunctive norm increased healthier food intake and we have also found that a message about approval of fruit and vegetable consumption did not affect eating behaviour (66) .…”
Section: Effect Of Norm Typesmentioning
confidence: 99%
“…We recently conducted two studies in which university students viewed flyers and posters about the daily fruit and vegetable intake of other students (66) . Participants either saw materials emphasising the health benefits of eating fruit and vegetables or information about fruit and vegetable eating norms.…”
Section: Experimentally Manipulating Non-context-specific Eating Normsmentioning
confidence: 99%
“…Studies on small samples of college students exist in the literature, but tend to be controlled experiments looking at high and low caloric intake as a reaction to a cue such as an informational flyer (Robinson, Fleming, & Higgs, 2014), papers (Berger & Rand, 2008;Berger & Heath, 2008) or information about what others ate (Yamasaki, Midzuno, & Aoyam, 2007).…”
Section: Introductionmentioning
confidence: 99%